On lower bounds for the approximation of individual functions by local splines with nonfixed nodes - Ligun, A. A.; Shumeiko, A. A.; Лигун, А. А.; Шумейко, А. А.; Лигун, А. А.; Шумейко, А. А. (Institute of Mathematics, NAS of Ukraine, 1999)
For functions with the integrable βth power, where β = (r + 1 + 1/p)−1, we obtain asymptotically exact lower bounds for the approximation by local splines of degreer and defectk ≥r/2 in the metric ofL p.